Computational intelligence in archaeology [ - Barcelâo, Juan A. (Information Science Reference, 2009)
"This book provides analytical theories offered by new and innovative artificial intelligence computing methods in the archaeological domain. This stimulating, must-have title is full of archaeological examples that allow academicians, researchers, and